2022
DOI: 10.1186/s12967-022-03765-1
|View full text |Cite
|
Sign up to set email alerts
|

Integration of CRISPR/Cas9 with artificial intelligence for improved cancer therapeutics

Abstract: Gene editing has great potential in treating diseases caused by well-characterized molecular alterations. The introduction of clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9)–based gene-editing tools has substantially improved the precision and efficiency of gene editing. The CRISPR/Cas9 system offers several advantages over the existing gene-editing approaches, such as its ability to target practically any genomic sequence, enabling the rapid development an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 155 publications
0
10
0
Order By: Relevance
“…Not to be overlooked in the future is the integration of CRISPR with other emerging technologies, such as microfluidics, nanomaterials, non-amplified reactions, and the field of artificial intelligence, to establish new assays to meet clinical needs. 145,146 In the course of this developmental journey, the ongoing exploration of CRISPR effector proteins holds promise as an exciting avenue for future research endeavours!…”
Section: Discussionmentioning
confidence: 99%
“…Not to be overlooked in the future is the integration of CRISPR with other emerging technologies, such as microfluidics, nanomaterials, non-amplified reactions, and the field of artificial intelligence, to establish new assays to meet clinical needs. 145,146 In the course of this developmental journey, the ongoing exploration of CRISPR effector proteins holds promise as an exciting avenue for future research endeavours!…”
Section: Discussionmentioning
confidence: 99%
“…This is followed by cell expansion and re-infusion to the patient. Infused CAR T cells determine anti-cancer immune responses, targeting cancer cells and tumor regression [13].…”
Section: Mrna-based Vaccinesmentioning
confidence: 99%
“…important in gRNA and CRISPR applications 41 . This method uses algorithms based on a growing gene editing data set reported globally and helps to predict activity and score gRNA features for best CRISPR performance 42 .…”
Section: Strategies Based On Artificial Intelligence and Deep Learnin...mentioning
confidence: 99%
“…to help predict important off-target effects of the CRISPR-Cas9 system 41 . The results of the studies have shown that the off-target effects of CRISPR, which may not always be random, may be prevented by the proper design of gRNA sequences 53 .…”
Section: Strategies Based On Artificial Intelligence and Deep Learnin...mentioning
confidence: 99%